Augmenting Architecture through Algorithmic Modeling - Nathan Howe (Oz, 2011)
Algorithmic modeling has infiltrated schools of architecture over the last few years. It promises to not only revolutionize the possibilities of form making but also to establish immediate work flows of fabrication that explore performative based outcomes.